Theories of Metaphor Revised Against a Cognitive Theory of Metaphor: An Apology for Classical Metaphor - Kessler, Stephan (Logos Verlag Berlin, 2018)
Research that deals with metaphors and linguistic imagery has increased in the last thirty years. However, studies that question existing theories of metaphor from a comparative perspective are less common. The reason for the present theoretical sketch was the metaphorical model of conceptualism, alias the cognitive theory of metaphor: at least with this theory, `metaphor' itself has become a metaphor, and the classical, rhetorical metaphor has been sidelined. Kessler's book not only criticises existing theories of metaphor, but also develops from them a discursive synthesis that seeks to rehabilitate the classical metaphor as an everyday pragmalinguistic phenomenon. For this purpose, the nature of thought, the mental lexicon, predication and word semantics are also covered.